An educational experience on collective memory and social justice in the Dominican Republic: a cultural-historical analysis - Rodríguez Arocho, Wanda C. (2022)
This research is a case study that presents the systematization of an educational experience in the Dominican Republic focused on the development of collective memory and social justice. This systematization represents a teaching strategy that promotes intergenerational dialogue on the experiences of a generation that lived through the historical and sociocultural context of Fulgencio Batista’s dictatorship, and young people who have learned about it through readings from the school curriculum and exposure to the mass media. The significance of the strategy lies in the identification and examination of concepts developed from a historical-cultural perspective linking education and human development. Key concepts include experience, the social situation of development, knowledge and identity backgrounds, and consciousness